Intruder alarms - Honey, G. (Newnes, 2007)
A comprehensive guide to the specification, selection, installation and maintenance of intruder alarm systems for technicians and security managers.- Resumé vydavatel
Previous edition: Oxford: Newnes, 2003.
Keywords: poplašná zařízení; poplachové a varovné systémy; signalizační zařízení; bezpečnostní detektory; zabezpečovací technika; elektrické zabezpečovací systémy; alarm equipment; alarm and warning systems; signalling devices; safety detectors; security technology; electronic security systems; elektronické knihy; příručky; electronic books; handbooks and manuals